Pengembangan Bahan Ajar SKI Berbasis LKS dan Mind Mapping untuk Memahami Materi tentang Wali Songo - Adib Qosim M; Evi Nur Halimah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop Islamic Cultural History (SKI) teaching materials based on Student Worksheets (LKS) and Mind Mapping for the Wali Songo topic and to examine their effectiveness in improving sixth-grade students’ understanding at MINU An Nur Purworejo. The research problem is students’ low comprehension of Wali Songo and limited engaging learning media. Using a simplified Borg & Gall R&D model, the study involved planning, product development, limited trials, revisions, and effectiveness evaluation. Thirty sixth-grade students participated in a one-group pretest-posttest design. Instruments included questionnaires, classroom observations, and concept comprehension tests. Results show a significant increase in average comprehension scores from 58.7 to 82.4. Observations and interviews reveal higher engagement, motivation, and systematic Mind Mapping skills. Findings confirm that integrating LKS and Mind Mapping enhances cognitive understanding, critical thinking, and information organization. The study contributes a practical, replicable teaching material model for elementary schools and highlights the importance of visual and interactive media to strengthen students’ understanding of Islamic cultural history.